Peacemaking referendums: the use of direct democracy in peace processes. Issue 5 (3rd July 2020) - Collin, Katherine
ABSTRACT: The use of referendums to forge, ratify and enact peace agreements is on the rise. In growing numbers, peacemakers have organized referendums in order to aid peace talks and ameliorate post-settlement peacebuilding. Despite this increasingly common practice, there is little consensus on whether referendums help or hurt peace. Such votes can be uniquely powerful tools for addressing sovereignty incompatibilities driving armed conflict. However, dangerous outcomes include mass violence, intensified polarization, and the undermining peace agreement implementation. Based on 31 case studies and elite interviews conducted in Colombia, Cyprus, East Timor, Indonesia, and South Sudan, this article elaborates an analytical framework for the uses of referendums in peace processes and identifies specific benefits and risks associated with differing types. I argue that referendums can improve peacemaking and conditions for implementing negotiated settlements when they are well-designed and well-implemented.